Some thoughts on renal failure flu - Arce, Julián (1919)
Between injuries and functional disorders that can cause flu, it is placed next to bronchopulmonary, cardiovascular and nervous determinations favorite of this infection, which have their seat in the kidneys and are likely to reach, intensity, clinical superiority capital to the point of imposing the prognosis and therefore constitute the most urgent and primary therapeutic indication. Recojidas Observations during the influenza pandemic, many countries still plaguing the globe show, indeed, the frequency of renal determinations of influenza, not just during the first febrile period frankly, paroxysmal, short and mild, 10 overall, of the disease, which resembles both dengue and sand fly fever, but also and especially in the second period, the period of complications.